Domestic and sexual violence against patients with severe mental illness. Issue 4 (March 2015) - Khalifeh, H.; Moran, P.; Borschmann, R.; Dean, K.; Hart, C.; Hogg, J.; Osborn, D.; Johnson, S.; Howard, L. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Domestic and sexual violence are significant public health problems but little is known about the extent to which men and women with severe mental illness (SMI) are at risk compared with the general population. We aimed to compare the prevalence and impact of violence against SMI patients and the general population. Method Three hundred and three randomly recruited psychiatric patients, in contact with community services for ⩾1 year, were interviewed using the British Crime Survey domestic/sexual violence questionnaire. Prevalence and correlates of violence in this sample were compared with those from 22 606 general population controls participating in the contemporaneous 2011/12 national crime survey. Results Past-year domestic violence was reported by 27% v. 9% of SMI and control women, respectively [odds ratio (OR) adjusted for socio-demographics, aOR 2.7, 95% confidence interval (CI) 1.7–4.0], and by 13% v. 5% of SMI and control men, respectively (aOR 1.6, 95% CI 1.0–2.8). Past-year sexual violence was reported by 10% v. 2.0% of SMI and control women respectively (aOR 2.9, 95% CI 1.4–5.8). Family (non-partner) violence comprised a greater proportion of overall domestic violence among SMI than control victims (63% v. 35%, p < 0.01). Adulthood serious sexual assault led to attempted suicide more often among SMI than control female victims (53% v. 3.4%, p < 0.001). Conclusions Compared to the general population, patients with SMI are at substantially increased risk of domestic and sexual violence, with a relative excess of family violence and adverse health impact following victimization. Psychiatric services, and public health and criminal justice policies, need to address domestic and sexual violence in this at-risk group.